FASE PENERAPAN SUMBER DAYA INSANIAH PADA PERUSAHAAN - Popy Novita Pasaribu * (Perbanas Journal of Islamic Economics and Business, 2021)
Companies that believe in values will be successful in the long run. These core values will give spirit or motivation to everyone in the organization and finally to the community in growing a human-centered monotheistic society 5.0. This article aimed to examine the phases of implementing the Islamic value-based HR Model in companies. The model used was the HR model with Islamic values and the meaning of prayer, as well as a harmonious corporate culture, resulting in the expected HR performance. This study used qualitative research methods with the object of research are two companies that have implemented Islamic values in managing the company. The technique of collecting data was triangulation, namely research instrument, in-depth interviews and secondary data analysis. Data analysis was inductive. The application of the Islamic value-based HR model goes through two phases, namely the "Mecca" phase and the "Medina" phase. Companies in the Mecca phase need to consistently carry out an integrated corporate culture internalization program, namely as values, decision-making patterns and attitudes. Internalization of culture by using Islamic values and the meaning of prayer to influence at the individual level, work units and companies in general can open hearts, minds and wills so that job satisfaction and employee commitment can be achieved. Companies in the Medina phase have shared values that have been entrenched and internalized which have an influence on HR performance. With the company's rapid development, culture as identity; fastener; a source of inspiration, pride and resources; driving force and as a pattern of behavior needs to be maintained and passed on to the next generation.